2000
DOI: 10.1007/s003300000553
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance scanning for classifying suspicious breast lesions: first results

Abstract: It has long been established that cancer cells exhibit altered local dielectric properties compared with normal cells. Consequently, different electrical conductivity and capacitance are measurable in malignant vs normal tissues. In this study we evaluated the reliability of electrical impedance scanning (EIS), a new technology, for the classification of suspicious lesions: differentiating benign from malignant, and as a primary means of detection of breast cancer. Fifty-two women with 58 sonographically and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 0 publications
0
59
0
3
Order By: Relevance
“…Therefore, the method is adequately sensitive to conductivity changes in malignant tissues. In previous studies they had reported 20-40 fold conductivity changes in benign versus malignant tissues in humans [2,3,4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the method is adequately sensitive to conductivity changes in malignant tissues. In previous studies they had reported 20-40 fold conductivity changes in benign versus malignant tissues in humans [2,3,4].…”
Section: Resultsmentioning
confidence: 99%
“…Radial. 10: 1555-1561(2000]. Therefore, in-vivo impedance imaging of suspicious lesions could aid in diagnosis of malignant tumors.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…A linear set of equations giving the relation between conductivity perturbations and magnetic flux density measurements around initial values is obtained: Ab = SAa (11) where Ab = b -bini is the change in magnetic flux density with respect to initial, S is the sensitivity matrix, and Aca = G -C'ini. S is calculated for known geometry, boundary conditions, and initial conductivity and given the measurements, Ab, conductivity is calculated.…”
Section: Image Reconstruction Improvementsmentioning
confidence: 99%
“…Electrical Impedance Scanning (EIS) is a new technique recently introduced to aid in the diagnosis of malignant breast tumors (10)(11)(12)(13)(14). The device that uses this technique generates a map of the conductivity distribution inside the breast tissue.…”
Section: Introductionmentioning
confidence: 99%